IL6 −174 G/C Promoter Polymorphism Influences Susceptibility to Mucosal but Not Localized Cutaneous Leishmaniasis in Brazil - Castellucci, Léa; Menezes, Eliane; Oliveira, Joyce; Magalhães, Andrea; Guimarães, Luiz Henrique; Lessa, Marcus; Ribeiro, Silvana; Reale, Jeancarlo; Noronha, Elza Ferreira; Wilson, Mary E.; Duggal, Priya; Beaty, Terri H.; et al. (The Journal of infectious diseases, 2006)
BackgroundMucosal leishmaniasis (ML) is associated with exaggerated tumor necrosis factor–α and interferon-γ responses and tissue destruction. ML follows localized cutaneous leishmaniasis (CL) caused by Leishmania braziliensis infection. Interleukin (IL)–6 down-regulates T helper (Th) cell type 1 differentiation and drives Th2 cell differentiation. The IL6 −174 G/C polymorphism is associated with proinflammatory diseases and IL-6 regulation MethodsThe −174 G/C polymorphism was genotyped in population samples and families with CL and ML from Brazil. Genotype frequencies were compared among patients with ML, patients with CL, and 2 control groups by logistic regression and family-based association test (FBAT) analysis. IL-6 levels were measured in macrophages ResultsThe C allele was more common in patients with ML than in patients with CL (odds ratio [OR], 2.55 [95% confidence interval CI, 1.32–4.91]; P=.005), than in patients who were leishmanin skin-test positive (OR, 2.23 [95% CI, 1.23–4.05]; P=.009), and than in neighborhood control subjects (OR, 2.47 [95% CI, 1.24–4.90]; P=.01). FBAT analysis confirmed an association between allele C and ML under both additive (z=4.295; P=.000017) and dominant (z=4.325; P=.000015) models. Significantly lower levels of IL-6 were measured in unstimulated macrophages from CC individuals than from GG individuals (P=.003) as well as after stimulation with soluble leishmania antigen (P=.009) ConclusionsIL-6 may regulate type 1 proinflammatory responses, putting individuals with low macrophage IL-6 levels at increased risk for ML